2016
DOI: 10.3109/13880209.2015.1131993
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the antidiarrhoeal properties of the aqueous extract and its soluble fractions of Chebulae Fructus (Terminalia chebula fruits)

Abstract: Context Chebulae Fructus is used as an herbal remedy for diarrhoea in traditional Chinese medicine. However, there is no scientific evidence to support its antidiarrhoeal activity. Objective This study evaluates the antidiarrhoeal properties of Chebulae Fructus aqueous extract (CFAE) and determines the active fraction. Materials and methods The antidiarrhoeal effect of CFAE (200-800 mg/kg) was investigated by determining the wet dropping, intestinal transit in BALB/c mice and enteropooling in Wister rats. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…A combination of these compounds in the given amounts could mediate the antidiarrheal activities of the EAF. Our results with pomegranate peels are similar to our results in a previous report showing that the main active constituents in Terminalia chebula fruits were corilagin and ellagic acid . Additionally, another report in the literature also showed that corilagin and ellagic acid are the 2 main components contributing to the antidiarrheal effect of Polygonum chinense Linn .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A combination of these compounds in the given amounts could mediate the antidiarrheal activities of the EAF. Our results with pomegranate peels are similar to our results in a previous report showing that the main active constituents in Terminalia chebula fruits were corilagin and ellagic acid . Additionally, another report in the literature also showed that corilagin and ellagic acid are the 2 main components contributing to the antidiarrheal effect of Polygonum chinense Linn .…”
Section: Discussionsupporting
confidence: 91%
“…Our results with pomegranate peels are similar to our results in a previous report showing that the main active constituents in Terminalia chebula fruits were corilagin and ellagic acid. 41 Additionally, another report in the literature also showed that corilagin and ellagic acid are the 2 main components contributing to the antidiarrheal effect of Polygonum chinense Linn. 29 Our reports and those of others indicate that these classes of compounds have antidiarrheal activities.…”
Section: Discussionmentioning
confidence: 99%
“…For example, gallic acid has been reported to possess wound healing properties [31] and constipating properties. Similar properties have been reported for fruits of other plants; for example, Terminalia chebula fruits, used as an herbal remedy for diarrhea in traditional Chinese medicine, also contain tannins, including gallic acid and related glycoside derivatives, as major components of the ethyl acetate fraction [32].…”
Section: Phytochemistrysupporting
confidence: 63%
“…The present study has demonstrated and characterized the effect of an aqueous suspension of the hydroalcoholic extract of bark from the (Sheng et al 2016). However, distinctively from these extracts, which inhibit the fluid accumulation in the intestinal lumen induced by castor oil, as seen in enteropooling assays in rats, eCl did not alter misoprostol-induced fluid build-up.…”
Section: Discussionmentioning
confidence: 75%